2019
DOI: 10.9734/ajaees/2019/v34i130188
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Agricultural Practices on Soil Organisms: Lessons Learnt from Market-gardens

Abstract: Intensive agriculture practices have an important impact on soil biota, which can affect dramatically soil quality. In order to limit this impact, alternative agricultural practices are more and more applied. However, these practices are still in progress and thus, it is necessary to investigate their impact on soil activity. In this context, we studied the impact of agricultural practices (intensive and agroecological) in vegetable cropping systems in Guadeloupe. The first aim of this study was to identify pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…According to Moulin et al, [23] the use of synthetic pesticides are widely spread among different farms. He went further to add that mulching has a major impact on soil fauna abundance and diversity.…”
Section: Cation Exchange Capacitymentioning
confidence: 99%
“…According to Moulin et al, [23] the use of synthetic pesticides are widely spread among different farms. He went further to add that mulching has a major impact on soil fauna abundance and diversity.…”
Section: Cation Exchange Capacitymentioning
confidence: 99%
“…These two cropping systems have been well studied in Guadeloupe compared to vegetable cropping systems [23]. In order to have a better understanding of the vegetable cropping systems in Guadeloupe, a previous study was conducted on the whole territory [24]. This study showed that the practices used by local market gardeners do not promote soil biodiversity and do not optimise soil functions.…”
Section: Introductionmentioning
confidence: 99%
“…This study showed that the practices used by local market gardeners do not promote soil biodiversity and do not optimise soil functions. Therefore, agroecological practices should be implemented in the vegetable production systems to contribute to the ecological transition of agriculture in this territory [24].…”
Section: Introductionmentioning
confidence: 99%